Fetal and neonatal alloimmune thrombocytopenia. Issue 1 (February 2016) - Zdravic, Darko; Yougbare, Issaka; Vadasz, Brian; Li, Conglei; Marshall, Alexandra H.; Chen, Pingguo; Kjeldsen-Kragh, Jens; Ni, Heyu
Summary: Fetal and neonatal alloimmune thrombocytopenia (FNAIT) is an alloimmune disorder resulting from platelet opsonization by maternal antibodies that destroy fetal platelets. The major risk of FNAIT is severe bleeding, particularly intracranial hemorrhage. Miscarriage has also been reported but the incidence requires further study. Analogous to adult autoimmune thrombocytopenia (ITP), the major target antigen in FNAIT is the platelet membrane glycoprotein (GP)IIbIIIa. FNAIT caused by antibodies against platelet GPIbα or other antigens has also been reported, but the reported incidence of the anti-GPIbα-mediated FNAIT is far lower than in ITP. To date, the maternal immune response to fetal platelet antigens is still not well understood and it is unclear why bleeding is more severe in FNAIT than in ITP. In this review, we introduce the pathogenesis of FNAIT, particularly those new discoveries from animal models, and discuss possible improvements for the diagnosis, therapy, and prevention of this devastating disease.